أهمية اللغة العربية للحفاظ على الموروث الإسلامي - Ahmad Hosin Khallaf; Kojin Kojin (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Al-Quran is Allah's revelation that was revealed to the Prophet Muhammad through the Angel Jibril to read, understand and practice. Al-Qur`an was come down in Arabic which is very fluent (clear) with a very high structure and style of Arabic. Likewise, the Messenger of Allah as the recipient of the revelation was the most eloquent human being so that the Companions were amazed by his fluency. Therefore Arabic has a very important role in safeguarding the two largest treasures in Islam.